Anaphylaxis and alternative medicine: an unexpected association. Issue 5 (October 2020) - Diaz, Sandra Gonzalez; Furci, Fabiana; Olivieri, Bianca; Ansotegui, Ignacio J.
Abstract : Purpose of review: The present review aims to evaluate the use of complementary medicine among patients with allergic disorders, highlighting the risk of adverse reactions, which are often not considered and referred by patients to specialists. Recent findings: Complementary medicine is often used in clinical practice and preferred by patients as it is considered a natural therapy compared to traditional medicine. This choice is because of various cultural and socioeconomics aspects. Summary: The use of complementary medicine and its adverse reactions, often as severe as anaphylaxis, is frequently reported in atopic patients, in which a cross reactivity between the natural herbs used and the pollen to which they are sensitized is possible. Therefore, a personalized approach in atopic patients before the use of natural products is crucial to prevent any adverse reactions.